The Relationship Between Certain Physical Properties and The Infiltration Rate of Ultisols in Oil Palm, Rubber, and Areca Nut Plantations in Maro Sebo Village, Jambi Luar Kota Subdistrict, Muaro Jambi Regency - Hasriati Nasution; Suryanto Suryanto; Yusfaneti Yusfaneti; Sri Mulyati (Sahabat Publikasi, 2026)
Ultisols are widely distributed in Indonesia and are commonly utilized for plantation activities, including oil palm, rubber, and areca nut cultivation. However, intensive land-use changes and management practices can affect soil physical properties, particularly infiltration processes, which are essential for regulating water availability, reducing surface runoff, and maintaining soil sustainability. This study aimed to evaluate the relationship between soil physical properties and infiltration characteristics of Ultisols under different plantation types in Maro Sebo Village, Jambi Luar Kota Subdistrict, Muaro Jambi Regency. The research employed a survey method with random sampling based on land use types and slope characteristics. Soil samples were collected from oil palm, rubber, and areca nut plantations, while infiltration measurements were conducted using a double-ring infiltrometer. The observed parameters included organic matter content, bulk density, total porosity, soil water content, infiltration rate, and infiltration capacity. Data were analyzed using the Horton infiltration model, independent-sample mean comparison tests, and multiple linear regression analysis. The results showed that rubber and areca nut plantations had better soil physical conditions than oil palm plantations, as indicated by higher organic matter content, lower bulk density, and greater total porosity. Areca nut plantations exhibited the highest infiltration rate, followed by rubber and oil palm plantations. Regression analysis revealed a strong relationship between soil physical properties and infiltration characteristics, with an average coefficient of determination (R²) value of 0.86. This study concluded that vegetation type and soil management practices significantly influenced the infiltration capacity of Ultisols. Therefore, sustainable plantation management practices are required to maintain soil physical quality and enhance water conservation functions.